The dimensional structure of students' self-concept and interest in science depends on course composition. (April 2019) - Jansen, Malte; Schroeders, Ulrich; Lüdtke, Oliver; Marsh, Herbert W.
Abstract: Both academic self-concept and interest are considered domain-specific constructs. Previous research has not yet explored how the composition of the courses affects the domain-specificity of these constructs. Using data from a large-scale study in Germany, we compared ninth-grade students who were taught science as an integrated subject with students who were taught biology, chemistry, and physics separately with regard to the dimensional structure of their self-concepts and interests. Whereas the structure of the constructs was six-dimensional in both groups (self-concept and interest factors for biology, chemistry, and physics), the correlations between the domain-specific factors were higher in the integrated group. Furthermore, the pattern of gender differences differed across groups. Whereas male students generally showed higher self-concept and interest in physics and chemistry, a small advantage for male students in biology was only present in integrated science teaching group. We conclude that aspects of the learning environment such as course composition may affect the dimensional structure of motivational constructs. Highlights: The composition of attended courses affects the structure of student motivation. Science self-concept and interest were less differentiated in integrated courses. These differences in construct structure also showed in differential gender effects.